Is Intelligent Design a Scientific Alternative to Evolution? The Catholic Church Teaching about evolution, creation and intelligent design - Pascual, L.C., Rafael (Alpha Omega, 2020)
Summary: The aim of this article is to clarify the epistemic status of the Intelligent Design proposal. We can consider it as an updated version of the classical ways of demonstrating the existence of God, in particular of the so-called “fifth way”. As such, it seems to be neither scientific nor properly theological, but rather a proposal at a rational-philosophical level. At the same time, it must also be made clear that the negation of purpose in evolutionary biological processes is similarly a philosophical position, not a scientific one. I propose to acknowledge this state of affairs and to reframe the debate at its proper level. On the argumentative level, it is just as wrong to neglect the controversy as it is to discredit one’s opponent. On the epistemic level, it is a mistake to present Intelligent Design as a scientific replacement for the scientific theory of evolution; it should be considered instead to be a genuine and serious alternative to the quasi-philosophical ideology of evolutionism. Key Words: evolution theory, evolutionism, Intelligent Design, existence of God, philosophy, sciences, theology. Sommario: Lo scopo di questo articolo è di chiarire lo stato epistemico della proposta dell’Intelligent Design. Possiamo considerarlo come una versione aggiornata dei modi classici di dimostrare l’esistenza di Dio, in particolare della cosiddetta “quinta via”. Come tale, non sembra essere né scientifico né propriamente teologico, ma piuttosto una proposta a livello razionale-filosofico. Allo stesso tempo, si deve anche chiarire che la negazione dello scopo nei processi biologici evolutivi è allo stesso modo una posizione filosofica, non scientifica. Propongo di riconoscere questo stato di cose e di riformulare il dibattito al livello adeguato. A livello argomentativo, è altrettanto sbagliato trascurare la controversia quanto screditare il proprio avversario. A livello epistemico, è un errore presentare l’Intelligent Design come un sostituto scientifico della teoria scientifica dell’evoluzione; dovrebbe invece essere considerato un’alternativa vera e seria all’ideologia quasi filosofica dell’evoluzionismo. Parole chiave: teoria dell’evoluzione, evoluzionismo, Intelligent Design, esistenza di Dio, filosofia, scienze, teologia. <iframe class="ginger-extension-definitionpopup" style="left: -80.3472px; top: -103.785px; z-index: 100001; display: none;" src="chrome-extension://kdfieneakcjfaiglcfcgkidlkmlijjnh/content/popups/definitionPopup/index.html?title=Summary&description=a%20brief%20statement%20that%20presents%20the%20main%20points%20in%20a%20concise%20form">